Phenotypic and genetic stability of new Indonesian melon cultivar (Cucumis melo L. ‘Melonia’) based on ISSR markers - BUDI SETIADI DARYONO; APRILIA SUFI SUBIASTUTI; ARVITA FATMADANNI; DIAN SARTIKA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Daryono BS, Subiastuti AS, Fatmadanni A, Sartika D. 2019. Phenotypic and genetic stability of new Indonesian melon cultivar (Cucumis melo L. ‘Melonia’) based on ISSR markers. Biodiversitas 20: 1069-1075. Cucumis melo L. ‘Melonia’ was new Indonesian melon cultivars produced by segregation of Meloni cultivar. The Meloni cultivar has a yellowish-skinned color, orange flesh fruit, and sweet taste. The stability of phenotype and genotype characters of this new cultivars were assessed using 27 morphological traits and 4 ISSR primers, respectively. Phenotype characters in F2 and F3 populations have been stable on 25 of 27 morphological traits used, except in weight of seed cavity and color of skin fruit. The 4 ISSR markers were produced 41 fragments, contained 28 monomorphic DNA bands and 13 polymorphic DNA bands. All of DNA bands were scored and used for genetic similarity analysis using MVSP 3.1A Program. The highest genetic variation was produced by UBC-808 primer with a polymorphic percentage of 38.46%. All of ‘Melonia’ populations were clustered together with 100% similarity percentage.  Compared to other cultivars, ‘Melonia’ had high similarity with ‘Meloni’ in 87.8%, meanwhile, ‘Melonia’ and Meloni cultivars had relationship with Melona at a similarity value of 70.7%.